Impulse Control Disorders and Related Complications of Parkinson's Disease Therapy - Lopez, Alexander M.; Weintraub, Daniel; Claassen, Daniel O. (Seminars in Neurology, 2017)
Impulsive and compulsive behaviors in Parkinson's disease (PD) patients are most often attributed to dopamine agonist therapy; dysregulation of the mesocorticolimbic system accounts for this behavioral phenotype. The clinical presentation is commonly termed impulse control disorder (ICD): Behaviors include hypersexuality, compulsive eating, shopping, pathological gambling, and compulsive hobby participation. However, not all PD individuals taking dopamine agonists develop these behavioral changes. In this review, the authors focus on the similarities between the phenotypic presentation of ICDs with that of other reward-based behavioral disorders, including binge eating disorder, pathological gambling, and substance use disorders. With this comparison, we emphasize that the transition from an impulsive to compulsive behavior likely follows a ventral to dorsal striatal pattern, where an altered dopaminergic reward system underlies the emergence of these problematic behaviors. The authors discuss the neurobiological similarities between these latter disorders and ICDs, emphasizing similar pathophysiological processes and discussing treatment options that have potential for translation to PD patients.
Keywords: Parkinson's disease; dopamine agonist; impulse control disorder; striatum